Morphological characterization of cacao cultivars in different socio-ecological settings of Ghana - Asare, E. (Georg-August-Universität Göttingen, 2022)
Knowledge of Theobroma cacao morphological variability provides the foundation for the utilization and conservation of genetic resources in Ghana. This study concentrated on cacao varieties, varietal richness and diversity maintained on farmers` fields. The objectives of the study were (1) to assess varietal richness per farm and the level of homozygosity of cacao cultivars on farmers’ fields through morphological analysis and farm management. (2) To identify existing cacao cultivars in the agroforestry system and compare them between organic and conventional farms. Ten agro-morphological characteristics were studied in 6 cacao cultivars. 387 individuals were surveyed in farmers´ fields belonging to Amelonado, Angoleta, Calabacillo, Cundeamor, Criollo and Pentagona cacao cultivars. Quantitative pod and beans traits included diameter at breast height, pod length and width, fresh pod weight, and bean fresh weight. Additional qualitative traits sampled were pod basal constriction, pod apex form, ripened and unripened pod color, and cotyledon color among others. Analysis of variance was used to determine the variations among cultivars. The dendrogram was generated to show the cluster relationship among cultivars. Simpson`s diversity index, varietal richness and Pielou`s evenness was computed under the IITA, organic and non-IITA cacao management systems in Ghana. From this study, Amazonian Forastero (Amelonado, Angoleta, Calabacillo, Cundeamor) and Criollo contributed to 99.7% of all cultivars studied. Cacao tree density ranged from 1,072 to 2,592 trees per hectare in conventional farms whilst organic farms recorded 736 to 2,240 trees per hectare. The diameter at breast height recorded ranged from 3.38 cm to 30.02 cm depending on the age of the cacao tree. There was no difference between leaf shapes found. Cacao cultivars differed significantly in terms of these quantitative traits; pod wall thickness, the weight of fresh beans, number of beans and beans width have each P < 0.001 as well as beans thickness (P < 0.01), while pod weight and beans length were not significantly different. In conclusion, a comprehensive understanding of the morphological relationship among the cultivars studied alongside information on allelic richness could be valuable in selecting core parents and for future breeding purposes.